Effect of the type of non-fibre carbohydrates in grass silage-based diets on in sacco ruminal degradability and protein value of lupin (Lupinus angustifolius L. cv. Sonet) seeds ground to different particle sizes - B. Niwińska; M. Andrzejewski (Czech Journal of Animal Science, 2011)
The study was conducted to find out the effects of the type of non-fibre carbohydrates (NFC) included in grass silage-based diets on in sacco degradability of dry matter (DM), crude protein (CP) and neutral detergent fibre (NDF) of lupin (Lupinus angustifolius L. cv. Sonet) seeds ground to different particle sizes. Measurements of degradability were carried out as a 3 × 2 × 3 × 3 experimental design of treatments with carbohydrates included in diets as primary sources of NFC (starch vs. pectin vs. sugars), particle size of ground seeds (1.0 vs. 5.7 mm), period of the trial (1 vs. 2 vs. 3) and cannulated cow (1 vs. 2 vs. 3). The variables of in sacco kinetics were calculated according to the equations of Ørskov and McDonald (1979) for degradation data corrected for the particle loss. The protein value of lupin seeds for ruminants was expressed as the amount of protein digested in the small intestine, and it was estimated based on the obtained characteristics of degradability. Under our experimental conditions, the type of NFC included in the grass silage-based diets and the particle size of seeds affected the course and extent of rumen degradation of lupin seed nutrients. Higher values of DM and CP degradation were estimated after 8 and 16 h of incubation (P < 0.05). The higher rate of degradation of insoluble but potentially degradable fractions (P < 0.05) and higher effective degradability (P < 0.05) were found out in the rumen of cows receiving diets containing sucrose compared with cows receiving diets containing starch. In comparison with starch and pectin, sucrose decreased the amount of protein digested in the small intestine (P < 0.05). The results suggested that the type of NFC determined ruminal microbial activity. An enlargement of the lupin seed particle size from 1.0 to 5.7 mm decreased the rumen degradability of lupin seed nutrients (P < 0.05) and increased the amount of protein digested in the small intestine (P < 0.05). The results indicated that feeding standards should consider the influence of the grinding level of lupin seeds in order to assess their nutritional value.